GLOBALNE PROMENE U SVETSKOJ PROIZVODNJI DUVANA - Filiposki, Kiril; Peshevski, Mile; Zivkovic, Dragic; Rajic, Zoran (Economics of Agriculture, 2018)
Nowadays, tobacco is produced in all continents, in 128 countries of the developed and non-developed parts of the world. In general, there are four main commercial types of tobacco: Virginia – 80%, Burley – 13%, Oriental – 4% and dark tobaccos – 3%. World tobacco production in 2009 was 7.193.007 t, which is 1.7 times higher compared to 1970. Production and consumption are greatly affected by the anti-smoking campaign led by WHO, which resulted in their global movement towards the developing countries. This process is also taking place in the Balkans area. Despite all bans and restrictions, tobacco production has not been reduced, but has a tendency to increase. The amount of tobacco production in the investigated period (1979 – 2009) had a cyclic movement: it increased until 1990, than decreased until 2006 and increased again since 2007.